Mesmerize is a dynamically adaptable user-friendly analysis platform for 2D and 3D calcium imaging data - Kushal Kolar (Nature Portfolio, 2021)
Calcium imaging is valuable for understanding neuro and cell biology, but is challenging to analyze, organize, and access. Here, the authors present an efficient, expandable and user-friendly platform, which encapsulates the entire analysis process all to way to interactive visualizations.